Decoding life expectancy gaps: a long-term decomposition analysis of three WHO European Region country groups - Umit Tleshova; Klára Hulíková Tesárková; Dagmar Dzúrová (Cogent Social Sciences)
Life expectancy at birth serves as a proxy measure of community health, indicating socio-economic development, healthcare accessibility, and the success of health policies. Observed differences in life expectancy among countries signal health inequalities, which should be addressed by developed societies.This study examines the development and variability of life expectancy at birth among three geographically, politically, culturally, but also climatically distinct groups of countries in the WHO EUR: Former Soviet Countries (FSC), Central & Eastern European Countries (CEEC), and Western European Countries (WEC), using data from the World Bank spanning from the mid-1960s to 2021. A quantitative analysis evaluated mortality disparities, applying the principle of mean differences in values of life expectancy at birth, both within- and between- the studied groups of countries. This method is used throughout the paper since it enables the study of long-term patterns over several decades, includes gender-specific analyses, and emphasizes internal diversity within each group. The results show that mortality disparities have either stayed constant or decreased gradually, with the largest life expectancy gap between FSC and WEC (over 12 years for males and nearly 10 years for females). CEEC countries exhibit significant internal heterogeneity, with some countries converging toward WEC levels, while others resemble FSC.These findings highlight the need for targeted strategies to address enduring health inequalities and enhance life expectancy in underperforming regions. This makes the methodology and the findings potentially important for stakeholders and policymakers in their efforts to achieve the 2030 Agenda’s goal of reducing health inequalities between countries.